Primary umbilical endometriosis: excision and neo-omphaloplasty - Roberto Luiz Sodré; Sérgio Toshio Yamamoto; Leonardo Gabeira Secco; Tenílson Amaral Oliveira; Corintio Mariani Neto (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Umbilical primary endometriosis is a rare condition that affects women of childbearing age. Spontaneous umbilical endometriosis presents lump in the navel, cyclic pain, discreet local bleeding during menstruation, with no history of previous surgery. The treatment is block excision of the lesion and umbilical cord with edges margin to avoid recurrence and immediate umbilical reconstruction. METHODS: We describe the surgical technique for circle excision of the umbilical endometrioma and neo-omphaloplasty in one stage. CONCLUSION: The possibility of umbilical endometriosis should be considered when the presence of nodules and umbilical bleeding, even without previous surgery. The surgical technique provides total remission of the lesion and an umbilical natural scar.